2022
DOI: 10.1007/s11657-022-01117-6
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to consider population screening for fracture risk in postmenopausal women? A position paper from the International Osteoporosis Foundation Epidemiology/Quality of Life Working Group

Abstract: Summary The IOF Epidemiology and Quality of Life Working Group has reviewed the potential role of population screening for high hip fracture risk against well-established criteria. The report concludes that such an approach should strongly be considered in many health care systems to reduce the burden of hip fractures. Introduction The burden of long-term osteoporosis management falls on primary care in most healthcare syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 152 publications
2
18
0
Order By: Relevance
“…In terms of total number of fractures, the end result would be that a large number of fractures would still occur in unprotected patients at risk and undermine achievable better public health results at the global population level. This triggers and further supports recent developments suggesting that a populationbased screening for fracture risk in postmenopausal women based on FRAX should be considered, in addition to the currently implemented high-risk case finding and treatment approach, for incorporation in many healthcare systems to reduce the burden of fractures [18,19].…”
Section: Discussionsupporting
confidence: 79%
“…In terms of total number of fractures, the end result would be that a large number of fractures would still occur in unprotected patients at risk and undermine achievable better public health results at the global population level. This triggers and further supports recent developments suggesting that a populationbased screening for fracture risk in postmenopausal women based on FRAX should be considered, in addition to the currently implemented high-risk case finding and treatment approach, for incorporation in many healthcare systems to reduce the burden of fractures [18,19].…”
Section: Discussionsupporting
confidence: 79%
“…When the analysis was confined to major osteoporotic fractures, screening resulted in a 9-10% significant decrease (Fig. 2B) [20]. More importantly, the largest impact of the three studies combined was on the rate of hip fractures; again bearing in mind the relatively small proportion treated, the meta-analysis showed a 20% reduction (HR 0.80, 95%CI 0.71-0.91) in hip fractures (Fig.…”
Section: Effectiveness Of the Screening Programmentioning
confidence: 87%
“…Both recognized, however, that the ability of screening to reduce hip fracture risk had some potential and since then a meta-analysis of three prospective, randomized controlled studies of FRAX-based screening has shown a significant reduction in hip fractures [19]. Whether or not osteoporosis, or more specifically high hip fracture risk, fulfils the criteria for screening has been addressed in a recently published position statement from the Epidemiology/Quality of Life Working Group (Epi/QoL WG) of the International Osteoporosis Foundation [20]. This editorial summarises the key issues relating to the proposed screening program.…”
Section: Introductionmentioning
confidence: 99%
“…The naïve use of national hospital record data has been a common practice for some time (13). Nonetheless,country-speci c FRAX fracture risk assessments based on register data have been developed for 77 countries (71). The assumptions and calculations underlying these predictions have not been published (72)(73)(74), limiting their relevance as a prediction tool (75,76).…”
Section: Discussionmentioning
confidence: 99%